Arendt among the machines: Labour, work and action on digital platforms - Charlton, Timothy (HannahArendt.net, 2025)
Questions of the modalities of production—of how we labour and how we work—reveal much about the shape and flow of our daily lives. The way in which we are productive is a sounding board for the deeper undercurrents of societal change itself. A thorough analysis of our working conditions can therefore reveal developing deficiencies in our capacity for political interaction before they unfold openly. Today, digitalisation is radically altering and expanding the meaning of work. The rise of digital platforms as intermediaries and market-makers has created a host of novel activities that defy easy categorisation as either labour or work, ranging from monetising property on rental portals, through piecemeal click work in digital factories, to influencing on social media. I argue that Arendt’s tripartite configuration of human activity as labour, work and action and its relationship with technology can be leveraged as an analytical lens to shine light on digital platform as a novel work environment. This article attempts three things: First, to develop an analytical lens for the study of technology based on Arendt’s tripartite understanding of human activity in The Human Condition. Second, to apply said model to two contemporary cases of digital platforms in society. Third, to propose how an Arendtian activity lens can be used to interrogate future technological developments in terms of their impact on political freedom. I thereby contribute a reading of the role of technology in The Human Condition, an aspect that has remained underexplored in the literature. Further, I demonstrate how forward-looking Arendt scholarship can be a relevant voice in the digital age.